Etnomedisin Karo di Sumatera Utara - Jamilah Nasution; Hanifah M.Z.N Amrul; Eva S. Dasopang (Jurnal Biologi Papua, 2022)
Indonesian medicinal plants have been documented for hundreds of years. The use of plants as traditional medicine is in great demand by the wider community, because medicinal plants are proven to be more beneficial for health. The Karo people use plants not only for traditional medicine, but also for daily needs such as food, customs and culture. The Karo people create a different system of local wisdom in caring for existing plants. The processing and use of this traditional medicine has been passed down by their ancestors. The traditional forms of Karo treatment that are always used are Parem/Yellow, Tawar, Karo Oil and Oukup. The four types of treatment have different characteristics and efficacy. Key words: ethnomedicine; Karo; local culture; medicinal plants.